Neural Cell Interactions with a Surgical Grade Biomaterial Using a Simulated Injury in Brain Organotypic Slices - Jessica Patricia Wiseman; Divya Maitreyi Chari (Journal of Functional Biomaterials)
Tissue engineering research for neurological applications has demonstrated that biomaterial-based structural bridges present a promising approach for promoting regeneration. This is particularly relevant for penetrating traumatic brain injuries, where the clinical prognosis is typically poor, with no available regeneration-enhancing therapies. Specifically, repurposing clinically approved biomaterials offers many advantages (reduced approval time and achieving commercial scaleup for clinical applications), highlighting the need for detailed screening of potential neuromaterials. A major challenge in experimental testing is the limited availability of neuromimetic, technically accessible, cost-effective, and humane models of neurological injury for efficient biomaterial testing in injury-simulated environments. Three dimensional (3D) organotypic brain slices bridge the gap between live animal models and simplified co-cultures and are a versatile tool for studies on neural development, neurodegenerative disease and in drug testing. Despite this, their utility for investigation of neural cell responses to biomaterial implantation is poorly investigated. We demonstrate that murine brain organotypic slices can be used to develop a model of penetrating traumatic brain injury, wherein a surgical-grade biomaterial scaffold can be implanted into the lesion cavity. Critically, the model allowed for examination of key cellular responses involved in CNS injury pathology/biomaterial handling: astrogliosis, microglial activation and axonal sprouting. The approach offers a technically simple and versatile methodology to study biomaterial interventions as a regenerative therapy for neurological injuries.